Kepuasan Pelanggan pada Kualitas Layanan Bengkel Amien Jaya Motor Bangkalan - Rahmatullah, Miftahul Amien; Wantara, Pribanus (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The aim of the study was to determine the effect of the dimensions of service quality which include tangibles, reliability, responsiveness, assurance and empathy on customer satisfaction at the Amien Jaya Motor workshop. This study used a quantitative method with a survey research type. This research was conducted at the Amien Jaya Motor Workshop involving 97 people or a questionnaire. Based on the results of the t test on tangible variables it has a significant effect on customer satisfaction while the t test on the reliability variable has a significant effect on customer satisfaction for the t test on the responsiveness variable also has a significant effect on customer satisfaction. In the t-test, the assurance variable has a significant effect on customer satisfaction, while in the t-test, the empathy variable also has a significant effect on customer satisfaction. Based on the results of the elaboration above, the quality of service which includes (Tangibles, Reliability, Responsiveness, Assurance, and Emphaty has a positive and significant simultaneous effect on customer satisfaction at Amien Jaya Motor (AJM) workshops). This can be proven by the results of the partial test (t test) the result shows that the f-count value is greater than the f- table so that it can be concluded that service quality affects customer satisfaction.